Transient analysis of a Markovian queue with chain sequence rates and total catastrophes. (26th May 2009) - Krishna Kumar, B.; Vijayakumar, A.; Sophia, S.
Queueing systems with state-dependent arrival and service rates along with catastrophes are investigated. Explicit expressions for the transient probabilities of system size are obtained. The corresponding steady-state probabilities are deduced. Busy period distribution is also found. Some performance measures are obtained for the system. Extensive numerical illustrations are provided. It is observed that the limiting distributions do not exist in the absence of catastrophes.